Researching of Properties of Gained Flame Retardancy on the Upholstery Leathers by Tributyl Phosphate Chemical - Safiye Meriç Açıkel (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Tributyl Phosphate (TBP) is classified asorganophosphorus compounds and shows a fire retardant effect in differentmaterials. In this work, TBP was applied to the non-finished upholstery leathersat different concentrations. (0%, 8%, 16%, 24%) After the flame retardantmixture applied to the leathers, samples were finished with a standardfinishing recipe. Fire retardant effect on TBP treated leathers was determinedby LOI test. Also morphological properties of leathers by SEM, molecularbinding characterization of leathers by ATR+FTIR Analysis and physicalproperties of leathers by Tensile Strength, Percentage Extension, Double EdgeTear Load, Thickness and Dry Rubbing Fastness were researched. The resultsshowed that TBP treated leathers have a good flame retardant effect and causedto reduce physical properties in allowable values.